2023
DOI: 10.1186/s13054-022-04292-7
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid as adjuvant treatment for convulsive status epilepticus: a randomised clinical trial

Abstract: Background Generalised convulsive status epilepticus (GCSE) is a medical emergency. Guidelines recommend a stepwise strategy of benzodiazepines followed by a second-line anti-seizure medicine (ASM). However, GCSE is uncontrolled in 20–40% patients and is associated with protracted hospitalisation, disability, and mortality. The objective was to determine whether valproic acid (VPA) as complementary treatment to the stepwise strategy improves the outcomes of patients with de novo established GCS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…For instance, the therapeutic dose of VPA was 14.42 mg kg −1 , which is significantly lower than the doses typically used in clinical trials (30 mg kg −1 for psychiatric diseases treatment). [36,37] Similarly, the cyclic pifthrin-𝛼 was transiently administered at a safe therapeutic dose of 1 μm to enhance cell proliferation. [38][39][40][41][42] Studies have confirmed that this treatment does not disrupt the tumor suppressor function of p53 signalling, [43] thus eliminating any potential oncogenic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the therapeutic dose of VPA was 14.42 mg kg −1 , which is significantly lower than the doses typically used in clinical trials (30 mg kg −1 for psychiatric diseases treatment). [36,37] Similarly, the cyclic pifthrin-𝛼 was transiently administered at a safe therapeutic dose of 1 μm to enhance cell proliferation. [38][39][40][41][42] Studies have confirmed that this treatment does not disrupt the tumor suppressor function of p53 signalling, [43] thus eliminating any potential oncogenic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Directly administering M7‐PNF into the dermis through local injection has been shown to enhance the efficacy and safety of the drug compared to intravenous administration. [ 36 ] Future research may explore the application of M7‐PNF through microneedling, dressing or creating a medical patch to enhance its clinical utility with improved efficiency and convenience in administration. Overall, our proteinaceous nanoformulation platform offers an advanced approach for in situ generation of native SwGs without the need for exogenous cell transplantation or gene manipulation, which has translational potential for clinical therapeutics.…”
Section: Discussionmentioning
confidence: 99%